2011
DOI: 10.1029/2011tc002890
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of a low‐angle extensional fault system from restored cross‐sections in the Northern Apennines (Italy)

Abstract: [1] Broad geological and geophysical documentation is available on regional extensional systems driven by low-angle normal faults. However, little information exists about the three-dimensional geometry and the offset distribution of such extensional structures. We present a new set of balanced geological sections across the extensional fault system driven by the Altotiberina low-angle normal fault in the Northern Apennines of Italy. We document this extensional system throughout a large set of surface (field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 89 publications
7
118
0
Order By: Relevance
“…This theory is supported by the evidence that no moderate-to-large magnitude earthquakes have been documented worldwide nucleating on LANFs using positively discriminated slip planes from the focal mechanisms (Jackson and White, 1989;Collettini and Sibson, 2001). On the contrary, observations of large displacements (Lister and Davis, 1989;John and Foster, 1993;Hayman et al, 2003;Collettini and Holdsworth, 2004;Jolivet et al, 2010;Mirabella et al, 2011) and the well-identified microseismic activity (Chiaraluce et al, 2007;Rietbrock et al, 1996) associated with these structures suggest that the LANFs are tectonically active, accommodating crustal extension and possibly formed at low angle. For these reasons, the LANFs cannot be excluded from the assessment of seismic hazard, although their inclusion still represents a debated issue.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This theory is supported by the evidence that no moderate-to-large magnitude earthquakes have been documented worldwide nucleating on LANFs using positively discriminated slip planes from the focal mechanisms (Jackson and White, 1989;Collettini and Sibson, 2001). On the contrary, observations of large displacements (Lister and Davis, 1989;John and Foster, 1993;Hayman et al, 2003;Collettini and Holdsworth, 2004;Jolivet et al, 2010;Mirabella et al, 2011) and the well-identified microseismic activity (Chiaraluce et al, 2007;Rietbrock et al, 1996) associated with these structures suggest that the LANFs are tectonically active, accommodating crustal extension and possibly formed at low angle. For these reasons, the LANFs cannot be excluded from the assessment of seismic hazard, although their inclusion still represents a debated issue.…”
Section: Introductionmentioning
confidence: 85%
“…The beach ball is the mechanism solution of the M w 5.1 1984 Gubbio earthquake (Westaway et al, 1989;Collettini et al, 2003). The red lines represent the projection at surface of the Alto Tiberina fault system (after Mirabella et al, 2011). The yellow arrows represent GPS velocities vectors in the last 10 years .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Civitello; 5.6 km depth) that is one of the deepest wells drilled by the Italian National organisation for Hydrocarbons (ENI). Borehole and laboratory P wave velocities (Trippetta et al, 2010(Trippetta et al, , 2013 have been integrated with P wave velocities obtained from best migration analysis of the seismic reflection profiles (Mirabella et al, 2011) and earthquake data collected by TABOO (Latorre et al, 2014) to develop a detailed one-dimensional velocity model for earthquake locations (Table 1).…”
Section: Site Selectionmentioning
confidence: 99%
“…They covered the area over the Alto Tiberina Fault, a low angle normal fault that acts as a basal seismic detachment and accommodates extensional deformation together with a complex normal fault system that is located in its hanging wall [9]. The structure bounds the western side of the upper Tiber Quaternary basin, and it is about 70 km long, dipping from 15˚ to 20˚ ENE [10]. It is clearly evident in the CROP03-NVR seismic reflection profiles [11] [12] [13].…”
Section: Signals Recorded By Cienmentioning
confidence: 99%